AN EXPLORATION ON STUDENTS’ PUBLIC SPEAKING ANXIETY: STIFIn PERSPECTIVE - Hz, Benni Ichsanda Rahman (LLT Journal: A Journal on Language and Language Teaching, 2022)
The purpose of this research is to examine the level of public speaking anxiety among students based on the differences in human intelligence machine division: STIFIn (Sensing, Thinking, Intuiting, Feeling, and Insting). This study involved 51 Management students who took the English for Specific course on their semester credits. This study employs a case study that is qualitative in nature. The data was gathered using a semi-structured approach. The data collected was then processed by using two methods: statistical calculations for quantitative data related to the results of filling out 17 Public Speaking Anxiety Scale (FLAS) questionnaires by students concerning their level of anxiety when performing a public speaking and constructive analysis for qualitative data related to the results of comparing respondents' responses. The results shows that students in the Insting personality have a higher average of public speaking anxiety: 51.60. Students who are Sensing have an average anxiety level of 49.25, whereas students who are Thinking have an anxiety level of 47.50. In comparison, Intuiting students have an average anxiety level of 48.66, while Feeling students have an average anxiety level of 50.17. Consider the implications, some suggestions are discussed to overcome the challenges.